LINGKUNGAN SEKOLAH DAN PEMBENTUKAN KESADARAN RELIGIUS SISWA MADRASAH IBTIDAIYAH: STUDI KASUS DI MIS AL-HUNAFA PALANGKA RAYA - Khoirulloh Luthfi Muhammad; Iqbal Nur Hilmi; Muhammad Fazry; Andika Putra; Surawan Surawan (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Character education at the Madrasah Ibtidaiyah level is a crucial formative phase, yet it is often confined to controlled classroom environments. This creates a sociological gap regarding how public open spaces can serve as catalysts for character building amidst the challenges of urban modernity in Palangka Raya. This study aims to analyze the utilization of the schoolyard at MIS Al-Hunafa Palangka Raya as a prophetic pedagogical instrument in shaping students' religious awareness. The primary focus is to describe the decentralization of religious activities through the